2021
DOI: 10.3390/cancers13164061
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chemotherapy in Vulvar Cancers: Time to Rethink Standard of Care?

Abstract: The actual role of chemotherapy in vulvar cancer is undeniably a niche topic. The low incidence of the disease limits the feasibility of randomized trials. Decision making is thus oriented by clinical and pathological features, whose relevance is generally weighted against evidence from observational studies and clinical practice. The therapeutic management of vulvar cancer is increasingly codified and refined at an individual patient level. It is of note that the attitude towards evidence sharing and discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…The role of adjuvant and neo-adjuvant therapies is believed to be mainly relevant in regional or distant disease. However, as Mazzotta et al suggested in their review, the level of evidence remains low and further research must be conducted to assess their real impact on survival and recurrence and to define the optimal tailored treatment strategy [26].…”
Section: Discussionmentioning
confidence: 99%
“…The role of adjuvant and neo-adjuvant therapies is believed to be mainly relevant in regional or distant disease. However, as Mazzotta et al suggested in their review, the level of evidence remains low and further research must be conducted to assess their real impact on survival and recurrence and to define the optimal tailored treatment strategy [26].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are no agreed protocols for the adjuvant treatment of VC—especially regarding the role of systemic chemotherapy; in fact, the choice of treatment is based on the assessment of pathological features such as DOI, surgical margin status, and nodal involvement [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients who underwent subsequent surgical treatment differed greatly in the published studies, between 20 and 100% of the patients. Complete pathological response was seen in 28.6–100% of the patients [3,19–32].…”
Section: Current Treatment Options For Locally Advanced Vulvar Cancer...mentioning
confidence: 98%
“…Again, chemotherapeutic regimens were highly heterogeneous. Chemotherapeutic agents used in these case series were bleomycin, methotrexaat, lomustine and cisplatin in various combinations [3,13].…”
Section: Andandmentioning
confidence: 99%
See 1 more Smart Citation